2022
DOI: 10.1111/1365-2435.13979
|View full text |Cite
|
Sign up to set email alerts
|

The active mouse rests within: Energy management among and within individuals

Abstract: The relationship between daily energy expenditure (DEE) and resting metabolic rate (RMR) provides insight into how organisms allocate energy to maintenance versus energetically expensive activities such as locomotor activity. Three models have been devised to describe energy management: the allocation, independent and performance models, which, respectively, predict a DEE–RMR slope of b < 1, b = 1 and b > 1. Here, we took paired repeated metabolic and behavioural measurements in 51 female white‐footed mice to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Since those POLS ideas were presented over a decade ago, there have been many empirical tests of the hypotheses, but few studies have found compelling evidence (e.g. [12][13][14]). Indeed, recent meta-analyses reveal little to no evidence for the POLS predictions at the among individual level ( [15][16][17] but see [18]).…”
Section: Current State Of Evidence For the Pace-of-life Syndrome Ideasmentioning
confidence: 99%
“…Since those POLS ideas were presented over a decade ago, there have been many empirical tests of the hypotheses, but few studies have found compelling evidence (e.g. [12][13][14]). Indeed, recent meta-analyses reveal little to no evidence for the POLS predictions at the among individual level ( [15][16][17] but see [18]).…”
Section: Current State Of Evidence For the Pace-of-life Syndrome Ideasmentioning
confidence: 99%
“…A typical 25 g laboratory mouse (or similar sized bird) at rest generates $1 mL CO 2 min À1 , [33][34][35][36][37] whereas a resting human (with a body mass 2500-fold larger than that of a mouse) generates $200 mL CO 2 min À1 . [38][39][40] In both of these species, as well as other animals, the actual rates of CO 2 production (hereafter: VCO 2 ) change from minute to minute depending on activity levels (and countless other experimental and physiological factors [41][42][43][44] ). For example, the VCO 2 of a resting mouse can increase by fourfold simply by reducing the ambient temperature from 30 to 10 C and inducing shivering thermogenesis.…”
Section: [Co ] In the Atmosphere And The Breathmentioning
confidence: 99%